Performance evaluation of Unresponsive flow Management on Server for better load rebalancing in Internet - Vijith, C; Azath, M (International Journal of Computer Sciences and Engineering, 2025)
Active Queue Management has specific role in computer networks. In this paper, we investigate the chances of Active Queue Management at serve side. The proposed system reduces packet loss ratio at server side to provide better load balancing at internal buffer levels. The system distinguishes responsive flows from unresponsive flows in a congested Hyper Text Transfer Protocol traffic, dynamically manages them and provides better transfer speed and maximum throughput in network.